A cross-sectional national survey of community pharmacy staff: Knowledge and antibiotic provision - Zawahir, Shukry (PLoS One, 2019)
BACKGROUND: Pharmacists’ knowledge about the clinical and legal aspects of antibiotic supply has an impact on appropriate dispensing practice. There are limited studies evaluating community pharmacists’ knowledge of antibiotic dispensing in low and middle-income countries, including Sri Lanka. We aimed (i) to evaluate community pharmacy staff’s self-reported knowledge about antibiotics and dispensing behaviour of antibiotics without a prescription, and (ii) to identify possible factors impacting their antibiotic dispensing behaviour. METHODS: A cross-sectional survey was conducted among a random sample (n = 369) of community pharmacies across all nine provinces in Sri Lanka using a self-administered questionnaire on their antibiotic knowledge and dispensing practice. Data were analysed using descriptive and inferential statistics including; t-test, one-way ANOVA or chi-square test, and binary and multiple logistic regression. RESULTS: A total of 265 pharmacy staff (210 (79%) pharmacists and 55 (21%) assistants) responded. Overall mean antibiotic knowledge score was 26.1 (SD 3.9; range 1–33, max possible score 34). The overall mean knowledge score t(263) = 2.41, p = 0.017, specific knowledge about antibiotic resistance (ABR) t(262) = 4.98, p = 0.021 and legal aspects of antibiotic dispensing χ(2)(1, N = 265) = 8.55, p = 0.003) were significantly higher among pharmacists than assistants. One in every three pharmacy staff reported that they dispensed antibiotics without a prescription on patient request; however the proportion was close to half when the patient was known to them. About 30% of the staff reported to have supplied antibiotics for minor infections in the week prior to the survey. However, there was no significant difference in the supply between pharmacists and assistants except for acute sore throat (12% vs 23%, respectively; p = 0.040). Those pharmacists with higher ABR knowledge were less likely to give out antibiotics without a prescription for viral infections in adults (Adj. OR = 0.73, 95% CI: 0.55–0.96; p = 0.027) and children (Adj. OR = 0.55, 95% CI: 0.38–0.80; p = 0.002). Awareness of legal aspects of antibiotic supply reduced overall dispensing (Adj. OR = 0.47, 95% CI: 0.30–0.75; p = 0.001), and specifically for bacterial infections in adults (Adj. OR = 0.45, 95% CI: 0.20–0.99; p = 0.047). Knowledge about antibiotic use and misuse reduced the likelihood of illegal dispensing for common cold (Adj. OR = 0.75, 95% CI: 0.60–0.94; p = 0.011) and acute diarrhoea (Adj. OR = 0.76, 95% CI: 0.58–0.99; p = 0.048). CONCLUSION: Despite the law prohibiting provision, antibiotic dispensing without a prescription continues in community pharmacies in Sri Lanka. Appropriate antibiotic dispensing was associated with high levels of pharmacists’ legal and clinical knowledge about antibiotics. Strategies to change the current practice are urgently needed.